TRANSFORMASI SASTRA LISAN KE DALAM SENI PERTUNJUKAN DI BALI: PERSPEKTIF PENDIDIKAN - I Ketut Sudewa (Humaniora, 2014)
Folklore is part of Balinese life. Although the existence of folklore in Bali has undergone some fluctuation, attempts have been made by the local government and society in Bali to preserve this cultural form. The aim is prevent folklore from extinction, especially because of the wave of globalization with its capitalistic force in order for the future generation of Balinese not to forget about their own culture. One of the efforts made by the Balinese government and society to preserve the existence of folklore in Bali is a competition called “Mesatue Bali”, run in the Bali arts festivals and other activities, and the publication of books. In the various competitions and performances of folklore, some form of transformation occurs from folklore to performance art. From an educational perspective, this transformation, especially for the young generation, means love and preservation, creativity, understanding of performance art, and character education. Performance art allows the young generation to understand more deeply and enact the characters, both good and bad, in folklore. Thus, they can follow the example of the good characters but not the bad characters.